Nonpsychotropic cannabinoid acts as a functional N-methyl-D-aspartate receptor blocker. - Feigenbaum, J J (1989)
Binding studies using the enantiomers of the synthetic cannabinoid 7-hydroxy-delta 6-tetrahydrocannabinol 1,1-dimethylheptyl homolog in preparations of rat brain cortical membranes reveal that the (+)-(3S,4S) enantiomer HU-211 blocks N-methyl-D-aspartate (NMDA) receptors in a stereospecific manner and that the interaction occurs at binding sites distinct from those of other noncompetitive NMDA antagonists or of glutamate and glycine. Moreover, HU-211 induces stereotype and locomotor hyperactivity in mice and tachycardia in rat, effects typically caused by NMDA receptor antagonists. HU-211 is also a potent blocker of NMDA-induced tremor, seizures, and lethality in mice. This compound may therefore prove useful as a nonpsychoactive drug that protects against NMDA-receptor-mediated neurotoxicity.